European Gigabit Society progress: how to stimulate further deployments of high-speed broadband networks? - Jesús Ferrandis; Sergio Ramos; Claudio Feijóo (International Telecommunications Society (ITS), 2023)
This paper examines the challenges and progress in meeting the European Gigabit Society's (EGS) targets for high-speed broadband networks and explores the implications of the new targets set for the Digital Decade (DD). With a focus on the availability of gigabit connectivity and 5G networks, the study analyses the existing gaps and their evolution from June 2017 to June 2021. The analysis highlights the significant disparity in broadband deployment, particularly in rural areas, where network operators and private investors face financial constraints and uncertainty regarding returns on investment. By utilizing the latest available data, this research estimates the remaining investment gap to achieve the EGS and DD targets and identifies areas where the gaps are most pronounced. Furthermore, the study assesses the probability of closing these gaps within the specified timeframe. The lack of transparency regarding specific areas and populations without coverage is identified as an additional hurdle for stakeholders and public-private initiatives seeking to initiate actions. In addressing these challenges, the paper proposes alternatives to facilitate network rollouts in rural areas, aiming to bridge the gaps and bring coverage closer to the EGS and DD objectives. This research sheds light on the state of broadband deployment, highlighting areas that face higher risks and challenges. By doing so, it contributes to our understanding of the feasibility of achieving the EGS and DD targets and provides valuable insights to inform strategies aimed at enhancing connectivity in underserved regions.
Keywords: 330